64.7k views
1 vote
Which of the following is equal to the rational expression when x ≠ -3?


(x^(2)-9 )/(x+3)

A. x + 3
B. x - 3
C.
(1)/(x-3)
D.
(x-3)/(x+3)

User Sefan
by
5.3k points

2 Answers

3 votes

Answer:

Choice B is correct answer.

Explanation:

We have given a rational expression.

x²-9 / x+3

We have to simplify the given expression.

Applying difference formula on the numerator of the expression, we have

a²-b² = (a-b)(a+b)

x²-9 = (x-3)(x+3)

x²-9 / x+3 = (x-3)(x+3) / x+3

x²-9 / x+3 = x-3 which is the answer.

User Pangamma
by
6.3k points
2 votes

Answer:

Option B (x - 3).

Explanation:

The given expression is
(x^(2)-9 )/(x+3) when x ≠ 3.

Here we know from the identity

(a² - b²) = (a - b)(a + b)

(x² - 9) = (x - 3)(x + 3)

Now the fraction is in factorized form


((x-3)(x+3))/((x+3))=(x - 3)

Therefore the given option B. (x - 3) is the correct answer.

User Dariux
by
5.4k points